2021
DOI: 10.3389/fped.2020.614097
|View full text |Cite
|
Sign up to set email alerts
|

A New Device for Thoracoscopic Cryoanalgesia in Pectus Excavatum Repair: Preliminary Single Center Experience

Abstract: Introduction: Cryoanalgesia has been recently described as alternative technique for immediate and persistent pain treatment after pectus excavatum repair. Cryoanalgesia has the potentiality to reduce analgesic consumption and length of hospitalization. However, cryoanalgesia has not been standardized yet: the previous reports describe different techniques and systems and include only small series. In Europe, no reports on cryoanalgesia for pectus repair have been published so far.Materials and Methods: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Although in most series a very small percentage of these are reported, Parrado et al reported that 9% of postoperative pneumothoraces in their study required a drainage tube or Sun et al reported a higher percentage of bar displacement in patients treated with PCr. 11,25 Different improvements have been designed to avoid this, such as the Parrado protective sheath, the use of a chest tube covering the cryoprobe described by Morikawa et al, or the use of a new cryoprobe reported by Torre et al 2,11,26 In our center, we eliminated the thoracoscopic approach and used the percutaneous approach with needle protecting the tissues with an angiocatheter so as not to damage them by contact and avoiding the risk of injury by contact of the cold with the lung, great vessels, or mediastinum by not entering the thoracic cavity. Our series reports no major intraoperative or postoperative complications during the cryoanalgesia process.…”
Section: Discussionmentioning
confidence: 99%
“…Although in most series a very small percentage of these are reported, Parrado et al reported that 9% of postoperative pneumothoraces in their study required a drainage tube or Sun et al reported a higher percentage of bar displacement in patients treated with PCr. 11,25 Different improvements have been designed to avoid this, such as the Parrado protective sheath, the use of a chest tube covering the cryoprobe described by Morikawa et al, or the use of a new cryoprobe reported by Torre et al 2,11,26 In our center, we eliminated the thoracoscopic approach and used the percutaneous approach with needle protecting the tissues with an angiocatheter so as not to damage them by contact and avoiding the risk of injury by contact of the cold with the lung, great vessels, or mediastinum by not entering the thoracic cavity. Our series reports no major intraoperative or postoperative complications during the cryoanalgesia process.…”
Section: Discussionmentioning
confidence: 99%
“…This type of probe was first time used for children in Poland. Previous type of straight probe was used in Italy, Spain, Argentina ( 16 ). The technical modification of the probe facilitates positioning.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies based on the application of thoracoscopic cryoanalgesia in MIRPE conclude a shorter hospital stay, reduced opioid consumption, and less pain compared with conventional techniques. 3,[9][10][11][12][17][18][19][20] As already described in the literature, the effect of cryoanalgesia can vary between 6 and 48 hours after application. In 2021, we conducted a study comparing patients in whom PCr was applied on the same day of PE surgery and those in whom it was applied 48 hours before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications have demonstrated a lower degree of pain, lower opioid consumption, and shorter hospital stay. [8][9][10][11][12] The novel and recent ultrasound-guided percutaneous approach is an efficient, safe, and reproducible procedure. It has advantages over the thoracoscopic approach by avoiding possible lesions due to thermal contact of the cryoprobe, less dissection, less thoracoscopy time, and in case of having to repeat the technique due to failure of the first application, the approach is less complicated.…”
Section: Introductionmentioning
confidence: 99%